Decoding MexB efflux pump genes: structural, molecular, and phylogenetic analysis of multidrug-resistant and extensively drug-resistant Pseudomonas aeruginosa - Habib, Muhammad Bilal; Shah, Naseer Ali; Amir, Afreenish; Alghamdi, Huda Ahmed; Tariq, Muhammad Haseeb; Nisa, Kiran; Ammoun, Mariam (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveEmerging drug resistance in Pseudomonas aeruginosa is of great concern in clinical settings. P. aeruginosa activates its efflux-pump system in order to evade the effect of antibiotics. The current investigation aims to detect MexB genes in P. aeruginosa, their structural and molecular analysis and their impact on antimicrobial susceptibility profiling.MethodsA total of 42 clinical specimens were aseptically collected from hospitalized patients who had underlying infections related to medical implants. Matrix-assisted laser desorption ionization-time of flight (MALDI-ToF) were used for the identification of isolates. The methods used in this study were antibiotic susceptibility profiling, minimum inhibitory concentration (MIC), polymerase chain reaction (PCR), sanger sequencing, phylogenetic analysis, MolProbity score, Ramachandran plot analysis and multiple sequence alignment.ResultsThe highest resistance was shown by P. aeruginosa against cefoperazone (67%), gentamycin and amikacin (66%) each, followed by cefotaxime (64%). The prevalence of multi-drug resistant (MDR) and extensively drug resistant (XDR) was 57% and 12%, respectively. The presence of an active efflux-pump system was indicated by the MexB genes found in most of the resistant isolates (p<0.05). Following addition of efflux pump inhibitor carbonyl cyanide m-chlorophenyl hydrazone (CCCP), a significant decrease (p<0.05) in MIC was observed in resistance, that revealed the presence of active efflux pump system. Phylogenetic analysis revealed evolutionary relationships with the P. aeruginosa strains isolated in Switzerland, Denmark and Germany. Protein domain architecture revealed that MexB gene proteins were involved in particular efflux pump function. Protein sequences aligned by multiple sequence alignment revealed conserved regions and sequence variants, which suggested antibiotic translocation and evolutionary divergence. These highly conserved regions could be used for diagnostic purposes of efflux pump MexB genes.ConclusionTo avoid their spread in hospital settings, responsible authorities ought to begin rigorous initiatives in order to reduce the prevalence of multi-drug resistant, extensively drug resistant, and efflux pump carrying isolates in clinical settings.